Chlamydia inhibits progesterone receptor mRNA expression in SHT-290 cells - Megan Brown; Mick Rae; Nick Wheelhouse (Bioscientifica, 2021)
Chlamydia trachomatis is the most commonly diagnosed sexually transmitted infection in the UK, with over 200,000 positive diagnoses annually. The infection is thought to cause reproductive complications including problems in conceiving a pregnancy through to miscarriage and early or stillbirth. One potential reason Chlamydia may impact upon pregnancy is through disrupting the embryo implantation at the earliest stages of pregnancy is by altering the ability of specific cells that line the uterus called stromal cells to respond to the hormone progesterone, the hormone responsible for preparing the uterus for pregnancy. The results of this study showed that Chlamydial infection of these uterus lining stromal cells decreased the levels of specific progesterone sensitive markers which are associated with early embryo implantation, suggesting a loss of responsiveness to progesterone treatment. These changes were accompanied by a decrease in the levels of RNA for the progesterone receptor which is responsible for progesterone activity, suggesting that this is a potential mechanism through which Chlamydia could directly inhibit the effects of progesterone on uterine cells.